PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SISTEM KONTROL ELEKTROPNEUMATIK DI SMK NEGERI 1 BATAM - Busra, Nelma; Jaenuddin, Jaenuddin (Jurnal Liga Ilmu Serantau, 2026)
This study aims to improve the learning outcomes of students in Grade XI Industrial Automation 3 at SMK Negeri 1 Batam through the implementation of the Project-Based Learning (PBL) model in the Electropneumatic Control Systems subject. This research employed classroom action research conducted in two cycles. The research subjects consisted of 41 students. Data were collected through learning outcome tests, observations, and documentation. The results showed that prior to the implementation of PBL, only 10 students (24.39%) achieved mastery learning with an average score of 59. In Cycle I, the number of students who achieved mastery increased to 23 students (56.10%) with an average score of 72. In Cycle II, the number of students achieving mastery further increased to 33 students (80.49%) with an average score of 79. These findings indicate a continuous improvement in students’ learning outcomes from the pre-cycle stage to Cycle II. Therefore, it can be concluded that the implementation of the Project-Based Learning model is effective in improving students’ learning outcomes in the Electropneumatic Control Systems.